Comparative studies of resistance on Indonesian Thin Tail (ITT) sheep, St. Croix, merino and the crossbreed of ITT and St. Croix, against the infection of Fasciola gigantica - S Widjajanti; S.E Estuningsih; S Partoutomo; J.A Roberts; T.W Spithill (Indonesian Center for Animal Research and Development (ICARD), 1999)
resistance is heritable. In order to re-evaluate this evidence, 20 ITT sheep were infected with 350 metacercariae of F. gigantica and for comparison, 10 St. Croix sheep, 10 Merino sheep and 20 crossbred of ITT x St. Croix sheep were also infected with the same dose of metacercariae. The results showed that ITT sheep was highly resistant than the other breed, whereas St. Croix and Merino sheep were susceptible. 60% of the crossbred were as resistant as ITT sheep and the other 40% were as susceptible as the St. Croix sheep. Thus, it is proposed that there might be a hereditary resistance factor such as a dominant gene which inducing the mechanism of resistance in ITT sheep, and there is some indication that IgG2 might act as a blocking antibody that interferes the mechanism of resistance. Key words : ITT sheep, Fasciola gigantica, genetic resistance, dominant gene